Nutmeg Shells Liquid Smoke Application for Yellowstripe Scad Fish Processing - Salindeho, Netty; Lumoindong, Frans (Jurnal Ilmu dan Teknologi Pangan, 2017)
This study aims to analyze chemical features of scad, Caranx sp., smoked using nutmeg shell liquid smoke. It used Â Complete Randomized Design under variation of liquid smoke concentrations and immersion duration. Â the former applied 30 minutes, 40 minutes, and 50 minutes immersion and the latter used 10%, 15%, and 20%. Results showed that 40 minutes immersion in 15% liquid smoke had the lowest water content and the highest protein content.Keywords: liquid smoking, nutmeg shell, scad